2013
DOI: 10.4049/jimmunol.1200993
|View full text |Cite
|
Sign up to set email alerts
|

Immunodeficiency and Autoimmunity in H2-O–Deficient Mice

Abstract: HLA-DO/H2-O is a highly conserved, nonpolymorphic MHC class II-like molecule expressed in association with H2-M in thymic epithelial cells, B lymphocytes, and primary dendritic cells. The physiological function of DO remains unknown. The finding of cell maturation-dependent DO expression in B lymphocytes and dendritic cells suggests the possibility that H2-O functions to promote the presentation of exogenous Ag by attenuating presentation of endogenous self-peptides. In the current study, we report that H2-O−/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 48 publications
5
40
0
Order By: Relevance
“…Thus, it was predicted that H2-O has evolved to control humoral immunity to self. However, although some elements of autoimmunity were previously reported in aged mice from one colony of H2-O-deficient ( H2-Oa −/− ) mice (Gu et al, 2013) it was not supported by other studies (Liljedahl et al, 1998). These contradictory results may indicate that the Ab response observed by Gu et al .…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Thus, it was predicted that H2-O has evolved to control humoral immunity to self. However, although some elements of autoimmunity were previously reported in aged mice from one colony of H2-O-deficient ( H2-Oa −/− ) mice (Gu et al, 2013) it was not supported by other studies (Liljedahl et al, 1998). These contradictory results may indicate that the Ab response observed by Gu et al .…”
Section: Discussionmentioning
confidence: 81%
“…Thus, we directly measured the impact of I/LnJ H2-Ob on MHC-II peptide presentation. Cells that lack H2-O have lower levels of MHC-II-CLIP complexes as H2-M function is enhanced in the absence of inhibition by H2-O (Gu et al, 2013) and MHC-II-CLIP levels on the cell surface can be used as a read-out to measure H2-M activity (Chen et al, 2002; Denzin et al, 1997; Glazier et al, 2002). Therefore, we used an Ab that specifically recognizes I-A b -CLIP complexes (Liljedahl et al, 1998) to measure H2-M activity in B cells from B6, B6.…”
Section: Resultsmentioning
confidence: 99%
“…Another non-classical class II molecule, HLA-DO (DO), also plays an essential role in antigen presentation in B cells (126129), as knockout of the murine DO homolog, H2-O, leads to immunodeficiency and autoimmunity that are directly related to dysfunction of antigen presentation by bone marrow-derived cells (130). Although DO is structurally quite homologous to classical MHCII, there is no evidence that it can directly present peptides.…”
Section: Generation Of the Mhcii/peptide Repertoire: Proteases And Rementioning
confidence: 99%
“…Next, we analyzed the generation of IgG AA, an indicator of a break in T cell tolerance [27]. Our initial analysis of permeabilized cell reactivity showed that seven of eleven cDKO mice had circulating IgG AA (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…WT plasma served as a negative control. Plasma from H2-O −/− deficient animals served as a positive control: these animals have been shown to develop IgG2a autoantibodies specific for nuclear antigens due to defects in MHC II presentation [27]. cDKO plasma samples demonstrated a diffuse pattern of IgM reactivity present in the cytoplasm with an apparent absence of nuclear staining (Fig.…”
Section: Resultsmentioning
confidence: 99%